On the onset and evolution of the Ross-orogeny magmatism in North Victoria Land - Antarctica - Giacomini F; Tiepolo M; Dallai L; Ghezzo C (Chemical Geology, 2007)
An extensive geochemical (major-, trace-element and oxygen isotope) and geochronological (U/Pb geochronology on zircon) characterisation of O1-bearing ultramafic-mafic cumulates and gabbro-diorites recently discovered in the southwestern region of the Wilson Terrane (North Victoria Land - Antarctica) was undertaken in order to constrain source characteristics, magma evolution and emplacement history in this sector of the Cambro-Ordovician Ross Orogeny. Textural and chemical data indicate disequilibria among mineral phases of these O1-bearing cumulate rocks. Corroded Cr-rich clinopyroxene with high Mg# (0.82) and Ca-rich plagioclase likely represent xenocrysts from an old magmatic system, and are not in equilibrium with the host cumulate assemblage (O1+Opx+Amp+Bt+Pl). The calculated liquid in equilibrium with the xenocrysts ("melt 1") exhibits exceptionally high La/Yb ratios and Th-U concentrations, suggesting a strong sediment influx in the mantle source, possibly from the subducted slab. Because of the extensive fractional crystallisation (Fo(70); Mg# = 76) and crustal contamination (e.g., delta O-18(Opx),= 7.13-7.47%(0).) the trace element composition of the liquid in equilibrium with the cumulate assemblage ("melt 2") does not reveal the nature of the mantle source not the differentiation processes. The gabbroic parental liquid for the main cumulate assemblage was not produced by ass:tmilation and fractional crystallisation (AFC) of the equilibrium "melt 1" calculated from the xenocrystic paragenesis. Rather, it likely represents a new pulse of magma originated from a different mantle source, which then evolved through AFC into gabbro-diorites. Zircon U-Pb dating of one gabbro-diorite yields a crystallisation age of 489 +/- 4 Ma. Zircon in the O1-bearing cumulates yielded two ages populations at 521 +/- 2 Ma and 502 +/- 3 Ma, which we interpret to represent the actual age difference between the two magmatic systems. This age difference suggests that poorly diffirentiated melts with adakite-type signature ...